If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 = 2(2w + -5) + 2w Reorder the terms: 46 = 2(-5 + 2w) + 2w 46 = (-5 * 2 + 2w * 2) + 2w 46 = (-10 + 4w) + 2w Combine like terms: 4w + 2w = 6w 46 = -10 + 6w Solving 46 = -10 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 46 + -6w = -10 + 6w + -6w Combine like terms: 6w + -6w = 0 46 + -6w = -10 + 0 46 + -6w = -10 Add '-46' to each side of the equation. 46 + -46 + -6w = -10 + -46 Combine like terms: 46 + -46 = 0 0 + -6w = -10 + -46 -6w = -10 + -46 Combine like terms: -10 + -46 = -56 -6w = -56 Divide each side by '-6'. w = 9.333333333 Simplifying w = 9.333333333
| (1/2)/3 | | 6(4a-2b)-4(-8a+6b)= | | 12x-4(x+y)-6y= | | x^4+2x^2-35=0 | | 28v^6-24v^3/4v^3 | | -45/-9 | | 3/5=-2/5x | | 2n+5n=220+3n | | 15x+36=8x-6 | | Z-0.9=2z | | 2(5-3s)+9=28 | | 5/7-1/4 | | 13+7=4+x | | a^2+b^2=50 | | -3x+3y=-18fory | | -2(k-2)-(8k-8)=-11k | | x^4-2x^2-14=0 | | 6ln(3x+6)=26 | | 9(x-7)=2+8x | | 2x^2+2=26 | | 15=2m-(9) | | 2.8=v/4 | | 5m^3/m^3 | | 7(x+4)=7x | | 8x-45=6x+15 | | -7=y-11 | | -8x-3+5x+4= | | 4x-2=1+3x | | 5x+1=5+6x | | x/4-6=2 | | Y+7/2+Y-17/9 | | 1/25-9z^3 |